Parents' perception toward the adoption of mobile application for monitoring their children's obesity status - Qasim, Mustafa Moosa; Zulkifli, Abdul Nasir; Ahmad, Mazida; Omar, Mazni; Abu Bakar, Juliana Aida (Asian Research Publishing Network (ARPN), 2015)
Obesity among children around the world has now reached an alarming level.Obesity affects one out of every ten children or teenagers all over the world. Parents should be the one responsible for their children well-being.With the advent of mobile technology, various mobile app have been developed to help people to manage their daily lives.This paper discusses on the development and evaluation of the Body Mass Index (BMI) Percentile Monitor, a mobile app for monitoring children's obesity status by parents.The results of the evaluation indicated that the parents highly rated the application in terms of usefulness, ease of use, hedonic motivation, outcome/future Use and satisfaction.